Early amniotic membrane transplantation for toxic keratopathy secondary to topical proparacaine abuse: a report of seven cases. (30th January 2013) - Burcu, Ayse; Dogan, Emine; Yalniz-Akkaya, Zuleyha; Ornek, Firdevs
Abstract: Purpose : The aim of this study is to evaluate the effect of early amniotic membrane transplantation (AMT) in patients with topical proparacaine-related toxic keratopathy. Materials and methods : Between 2008 and 2011, eight eyes of seven patients with toxic keratopathy related to 0.5% proparacaine abuse underwent early AMT (within 1 to 5 days following the diagnosis). Clinical findings and treatment outcomes of these cases were evaluated retrospectively. Results : The median time of topical anesthetic abuse until admission to our clinic was 28 (10–112) days. One case was referred due to achanthamoeba keratitis; two cases due to intractable corneal ulcer and melting. At initial examination, visual acuities varied between hand motions and 0.4 (in decimal notation). Biomicroscopic evaluation at presentation revealed epithelial defects, corneal ulcers, stromal ring infiltrate, stromal edema and corneal melting with varying degrees. At third month after AMT, the visual acuities varied between hand motions and 0.9, and all the patients had corneal stromal opacities with varying densities. One patient, who did not respond to medical and surgical treatment and developed secondary infections that invaded intraocular structures, underwent evisceration. Conclusion : Topical anesthetic abuse can lead to serious ocular complications. After proper diagnosis, the first step of treatment is the cessation of drug abuse. In addition to medical treatment, early AMT has an advantage of early pain relief and consequential elimination of the need for topical anesthetic instillation.